A Rare Parasite in Cats: Record of a Linguatula serrata Frölich, 1789 (Porocephalida, Linguatulidae) Nymphal Infestation in a Cat in Albania, with a Synopsis and Review of the Literature on L. serrata Infestation in Cats - Enstela Vokshi; Martin Knaus; Steffen Rehbein (Biology)
Linguatula serrata, commonly known as the dogs’ ‘tongue-worm’, is an arthropod endoparasite of the class Pentastomida infesting chiefly canids as definitive hosts and herbivores as intermediate hosts. Adult L. serrata usually reside in the upper respiratory tract, such as the nasal cavity and sinuses, and the larval stages are encapsulated in various visceral organs, respectively. This report presents the first case of a L. serrata nymphal pulmonary infestation in a cat from Albania and adds to the description of the overall rare cases of this parasitic infestation in domestic cats. Discussion of this case together with a comprehensive review of the literature allows us to conclude that cats are susceptible to the infestation with L. serrata when ingesting the parasite’s eggs and allow for the development of the nymphal stage of the parasite in several visceral organs. Therefore, cats may serve as accidental intermediate hosts in the life cycle of L. serrata but are unlikely to be of epidemiological relevance. There is no evidence that domestic cats can act as definitive hosts of L. serrata.